Effect of silvicultural treatments on the growth of Thyrsostachys siamensis (gamble) at Wetland Putrajaya, Malaysia - Mohamed, Azmy; Loy, Bee Yen (2008)
Thyrsostachys siamensisis is considered as one of the commercial species which can be utilized as food from its shoot. Its culm are used for multiple purposes, such as for building materials, furniture, farm implements, mats and baskets. Besides, it can be used as an ornamental plant to reduce soil erosion and provide shade. This species has the potential also in producing as pulp and paper. In Malaysia, there is no study done on the silvicultural treatment of this species. A study on the silvicultural treatments on the growth of Thyrsostachys siamensis at Wetland Putrajaya was done. This research was done to determine the effect of organic fertilizer (goatgro) and thinning on the growth performance of Thyrsostachys siamensisis Gamble. Six different treatments were applied. A constant goatgro fertilizer’s rate of 2 kg using pocket system combined together with three thinning regimes of 0, 15 and 30% were applied on various assigned clumps available. Each replicate was assigned to 4 clumps and there were six replicates altogether comprising a total of 24 clumps. The data was collected for every 3 days in week. The parameters measured were, the number of shoots and culms, shoot’s and culm’s height. Results from this research showed that there was a positive effect on the growth performance of this species due to the treatments. Thinning 30% of Thyrsostachys siamensis’s culm gave an effect to the new shoots sprouted. By applying organic fertilizer, it gave a positive effect on the shoot’s and culm’s height.